Analysis of Academic Cooperation Network for Returnee Faculty Members to Realize Value from the Perspective of Economics - Yanchun Zhu; Fuze Li; Chunlei Qin; Wei Zhang; Jianbo Wen (Discrete Dynamics in Nature and Society)
Drawing on theories of social network and knowledge absorption, this paper examines the direct influence of returnee faculty members (RFMs) over college research performance (CRP) from three aspects, namely, the intensity of cooperative relationship (ICR), research influence (RI), and acquisition capability of heterogeneous knowledge (ACHK). In addition, the authors tested the regulating effect of ICR. The results show that RI of RFMs has a significant positive effect on CRP, ACHK has no significant effect on CRP, and ICR has a significant negative effect and a major regulating effect on CRP.